Configuration of Atypical Scabies as The Great Imitator - Reqgi First Trasia (Universitas Sultan Ageng Tirtayasa, 2022)
Scabies is still remaining a public health problem, especially in temperate regions tropical and subtropical. WHO includes scabies as a Neglected Tropical disease that needs large-scale control. There are various forms of atypical scabies that are difficult to identify which can lead to a misdiagnosis. This misdiagnosis also leads to the untreated well. The purpose of this article is to review the configuration of scabies as the great imitator. The atypical forms of scabies are scabies of cultivated, incognito scabies, nodular scabies, blouse scabies, animal transmitted scabies, bedridden scabies, scabies on AIDS patients, scabies with STD coinfection, scabies on baby and elderly, and crusted scabies. Among these forms, crusted scabies is the latest in diagnosis, and it often results in outbreaks at the endemic area.